ALK and GSK3: Shared Features of Neuroblastoma and Neural Crest Cells. (August 2018) - Gonzalez Malagon, Sandra G; Liu, Karen J
Neuroblastoma is one of the most common and deadly childhood cancers. Neuroblastoma arises from transformed cells of the neural crest lineage. Outcomes of the disease vary greatly, ranging from spontaneous regression to aggressive metastases. While this variability may reflect the inherent migratory capabilities and multipotency of neural crest cells, there have been few direct comparisons between neuroblastoma and embryonic neural crest cells, in part because of the limited in vivo accessibility of the mammalian neural crest lineage. Our recent studies demonstrate a novel link between anaplastic lymphoma kinase (ALK) and glycogen synthase kinase 3 (GSK3). Our work suggests that ALK-dependent regulation of GSK3 via tyrosine phosphorylation may alter the substrate specificity of GSK3, thus regulating cytoskeletal dynamics in migrating neural crest cells.